2019
DOI: 10.3892/mmr.2019.10659
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA MEG3 suppresses the growth of glioma cells by regulating the miR‑96‑5p/MTSS1 signaling pathway

Abstract: Glioma is one of the most common types of tumor of the central nervous system with high mobility and mortality. The prognosis of patients with high-grade glioma is poor. Therefore, it is urgent to develop the therapeutic strategies for the treatment of glioma. Long non-coding RNAs (lncRNAs) have been reported as potential inducers or suppressors of numerous types of tumors including glioma. Previous studies have revealed that lncRNA maternally expressed gene 3 (MEG3) is involved in the initiation and progressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 48 publications
0
32
0
Order By: Relevance
“…Subsequently, lncRNA MEG3 expression was found to be downregulated in glioma tissue cells. Zhang et al (10) reported that lncRNA MEG3 inhibited glioma cell growth in vitro by regulating the mir-96-5p/MTSS1 signaling pathway, and was involved in cell proliferation and apoptosis regulation. Earlier studies indicated that lncRNA MEG3 also showed a downregulated trend in the brain tissues of patients with Huntington's disease, and Meg3knockout affected the expression of genes in the cerebral cortex of mice, leading to increased cortical microvascular density and enhanced expression of genes related to angiogenesis (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, lncRNA MEG3 expression was found to be downregulated in glioma tissue cells. Zhang et al (10) reported that lncRNA MEG3 inhibited glioma cell growth in vitro by regulating the mir-96-5p/MTSS1 signaling pathway, and was involved in cell proliferation and apoptosis regulation. Earlier studies indicated that lncRNA MEG3 also showed a downregulated trend in the brain tissues of patients with Huntington's disease, and Meg3knockout affected the expression of genes in the cerebral cortex of mice, leading to increased cortical microvascular density and enhanced expression of genes related to angiogenesis (19).…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs are protein-free transcripts, but occupy a large part of the transcription output. They are involved in the regulation of epigenetic, transcription, and post-transcriptional processing in cell homeostasis, and have attracted increased research attention in biomedicine, with particular focus of the roles of lncRNAs in normal neurodevelopment and neurogenerative diseases (including Alzheimer's disease, Huntington's disease, and PD) (10,11). However, this field is still in its infancy, and the function of most identified lncRNAs remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The role of MEG3 in cancers has been reported in several studies in which the interaction between lncRNAs, miR and mRNA, has been highlighted [26,27]. In glioma, MEG3 inhibited the proliferation, migration and invasion of glioma cells by regulating miR-96-5p/MTSS1 [28].In multiple myeloma, MEG3 inhibited tumor progression through regulating the miR-181a/HOXA11 axis [29].Particularly, previous studies have suggested that MEG3/miR-9-5p is involved in regulating the progression of prostate cancer and esophageal cancer by targeting QKI-5 and FOXO1. Recently, a study by Liu et al found that MEG3 can serve as a ceRNA for miR-9-5p to mediate the development of HCC through upregulating SOX11 [30].To further explore the molecular mechanisms underlying the role of MEG3 in HCC, we investigated whether MEG3 exerts its protective effects in HCC via regulating miR-9-5p/MDK axis.…”
Section: Mmp1 Is Involved In Invasion and Metastasis During The Develmentioning
confidence: 97%
“…In addition, downregulation of MEG3 was also observed in human glioma cell lines, compared with normal astrocytes. The promoting effects of miR-96-5p on cell growth and metastasis can be reversed by upregulation of MEG3 [65]. Moreover, Wang et al showed that the expression of MEG3 inhibits cell proliferation and results in G0/G1 arrest in human glioma cell lines through association with p53 [21].…”
Section: Megmentioning
confidence: 99%